Cortical structure and episodic memory profiles in APOE ε4: Resilience and vulnerability for cognitive impairment. (December 2021) - Coughlan, Gillian; Zhukovsky, Peter; Voineskos, Aristotle N; Grady, Cheryl
Abstract: Background: The apolipoprotein E (APOE)‐ε4 allele represents the greatest genetic risk factor for late‐onset Alzheimer's disease (AD). Identifying a resilience profile that might mitigate medial temporal lobe atrophy in enriched genetic risk may explain differences between individuals' susceptibility to AD pathology. Method: 742 older adults from OASIS‐3 were stratified by APOE genotype status (423 ε3ε3 carriers; 271 ε3ε4 carriers and 48 ε4ε4 carriers) and classified as cognitively normal (74%) or with mild cognitive dysfunction (26%) using the clinical dementia rating scale (CDR) score. Neuropsychological screening measured general cognitive function, depression and psychiatric symptoms. Episodic memory, processing speed and naming ability were included as cognitive outcome measures. Cortical structure was measured using FreeSurfer. General linear models determined the main effects of APOE and cognitive status on relative regional volumes (regional volume divided by total intracranial volume) and cognition. APOE x cognitive status interactions were followed up with linear models to assess the effects of APOE in the cognitively normal and impaired groups separately. Result: As expected main effects of APOE and cognitive status were observed on hippocampal, amygdala and entorhinal volumes. Greater effects of APOE were found on all regions in individuals with cognitive dysfunction, except on the entorhinal cortex. Significant interactions between APOE and cognitive status revealed that the left precuneus and superior frontal volumes were preserved in cognitively normal homozygote and heterozygote ε4 carriers with entorhinal atrophy, but were reduced in cognitively impaired ε4 carriers, controlling for age and sex. We found a similar interactive effect of APOE and cognitive status on episodic memory, with superior memory in cognitively normal e4ε4 carriers, and memory impairment in cognitively impaired e4ε4carriers, compared to their respective cognitive normal and impaired ε3ε3 counterparts. Conclusion: Cortical and subcortical atrophic signatures were identified for cognitively normal and impaired ε4 carriers. Structural integrity of the precuneus and superior frontal cortices may protect against cognitive dysfunction, even if medial temporal atrophy is present. Thus, our results indicate that the structural integrity of frontal‐parietal lobes may provide resilience against cognitive impairment in the face of ε4‐related decline in medial temporal structures.